Appropriate Climate Smart Technologies for Smallholder Farmers in Sub-Saharan Africa - Sullivan, Amy; Mumba, Aliness; Hachigonta, Sepo; Connolly, Mike; Sibanda, Lindiwe Majele (FANRPAN, 2013)
Nearly 70 per cent of the population in Sub-Saharan Africa (SSA) live in rural areas and rely mainly on agriculture for livelihood security. Low agricultural productivity in the region keeps this population under constant pressure, even though investment in agriculture is a proven way to reduce regional poverty. Studies have shown that Gross Domestic Product (GDP) growth in agriculture is at least twice as effective in reducing poverty as GDP growth originating outside agriculture. It is therefore necessary to develop and implement appropriate agricultural policies to support proven practices to alleviate poverty in this region where the majority of the population live on less than US$ 2 per day.